Anthropological Approach in The Study of Islam - Maryamah, Maryamah; Fitri Oviyanti; Khaf Shah; Nurjana; Abdul Nasir (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research aims to understand religion through its evolving practices within society, utilizing an anthropological approach. The primary objectives of this study are to explore and analyze three aspects: a profound understanding of the anthropological approach in Islamic studies in terms of etymology and terminology, the analysis of methods, techniques, and research steps using an anthropological approach, and a comprehensive examination of research outcomes employing anthropological approaches in Islamic studies. This research adopts the library research method, collecting literature data from 10 books and 10 journals relevant to the research topic. The results of this study involve an in-depth analysis of various anthropological approaches applied in Islamic studies.The anthropological approach in Islamic studies represents a profound and intricate method for understanding Islam within the context of human social and cultural dynamics. By considering various anthropological paradigms, researchers can explore the diversity of religious practices, analyze symbolic meanings, understand social interactions, and investigate conflicts that arise within Muslim communities. Through holistic, micro, semiotic, comparative, and behavioristic approaches, anthropological research in Islamic studies opens doors to comprehend the complex and often contradictory dynamics in the lives of Muslims. Consequently, this research not only provides deep insights into Islam as a religion but also into humans as complex social and cultural beings. By understanding Islam through the lens of anthropology, we can respond to global and local challenges with a more profound and contextual understanding of the values, beliefs, and religious practices of Muslims worldwide.